2022
DOI: 10.3390/polym14142917
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Removal of Methylene Blue by Bio-Based Sodium Alginate/Lignin Composite Hydrogel Beads

Abstract: Dye pollution is a serious issue in current environment protection, and bio-based adsorbents have been receiving much attention in wastewater treatment, due to their low cost, renewable, and environmentally friendly characteristics. Bio-based sodium alginate/lignin composite (SA/Lig) hydrogel beads were fabricated by a facile cross-linking with calcium ion and used for the removal of methylene blue (MB). The obtained SA/Lig microbeads were characterized with SEM, FTIR, and TG, and the effect of lignin content,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
(80 reference statements)
1
18
0
Order By: Relevance
“…The increased aromaticity of the material enhances this mechanism. The π–π electron donor–acceptor interactions are also important during the adsorption of dyes, e.g., methylene blue or red congo, on BC [ 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increased aromaticity of the material enhances this mechanism. The π–π electron donor–acceptor interactions are also important during the adsorption of dyes, e.g., methylene blue or red congo, on BC [ 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the adsorption kinetics of various P@SiO 2 nanocomposite doses were described very well with the pseudo-second-order. For this model, it is suggested that the rate-limiting step might be chemical adsorption for the adsorption of MB dye onto P@SiO 2 nanocomposite [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption, among the techniques, is the most powerful, economical, and efficient technique utilized to decontaminate dyes from wastewater at low concentrations due to its simplicity, low cost, and not requiring advanced technology [ 10 , 11 , 12 , 13 ]. During this year, novel adsorbent materials have been reported to remove toxic dyes such as methylene blue from wastewater [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Activated carbon (AC) is one of the most traditional, effective, and extensively utilized adsorbents in adsorption technologies, and it is among the cheapest sorbents in market.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used to immobilize entities, such as metal ions and medicine, via numerous hydrogen and coordination bonds. 15 However, little research has been done about its restriction for AIE.…”
Section: Introductionmentioning
confidence: 99%